Climate effects of management intensity and rotation length for planted pine systems - Sarah J. Puls; Justin S. Baker; Rachel L. Cook; James L. Rakestraw (Mitigation and Adaptation Strategies for Global Change, 2026)
Managed forests, including plantation systems, play a vital and often underappreciated role in contributing to the global carbon sink and mitigating climate change, and determining the most effective mitigation strategies requires accounting methods that accurately assess the climate effects of forests. We use a dynamic life cycle assessment methodology to compare the climate effects of thirty-six forest management scenarios (varying site productivity, planting density, fertilization, and thinning) with varying rotation lengths for loblolly pine plantations in the southern U.S., including both in situ and ex situ greenhouse gas fluxes. We also evaluate the effectiveness of using only carbon stock estimates to assess the net climate effect of a given management regime relative to radiative forcing metrics. Carbon stocks alone failed to accurately portray the climate effects from different management regimes, emphasizing the need for greenhouse gas accounting methodologies that directly represent the effect of forest management on potential atmospheric warming mitigation efforts. When radiative forcing is used for comparison, our results show that management decisions such as thinning and rotation length should be adjusted based on stand-specific conditions, and that overgeneralized strategies, such as extending rotation lengths, had little effect on net radiative forcing for many scenarios.